Anatomical Variations of the Jugular Foramen Region in Patients with Pulsatile Tinnitus - Li, Lifeng; Yang, Bentao; Ma, Xiaobo; Li, Pingdong; Creighton, Francis X.; Carrau, Ricardo L.; London, Nyall R., Jr. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Structural anomalies of the jugular foramen (JF) and adjacent structures may contribute to development of pulsatile tinnitus (PT). The goal of this study was to assess anatomical variants in the ipsilateral JF region in patients with PT and to explore possible predisposing factors for PT.Methods One hundred ninety-five patients with PT who underwent CT angiography and venography of the temporal bone were retrospectively analyzed. Anatomic variants including dominance of the ipsilateral JF, bony deficiency of the sigmoid sinus and internal carotid artery canal, high riding or dehiscent jugular bulb, dehiscence of the superior semicircular canal, tumors in the JF region, or cerebellopontine angle were assessed.Results Of 195 patients with PT, the prevalence of a dominant JF on the ipsilateral side of patients with PT was 67.2%. Furthermore, the dominant JF demonstrated a significant correlation with the presence of ipsilateral PT (p < 0.001). No anatomical variants were present in 22 patients (11.3%), whereas in patients with structural variants, bony deficiency of the sigmoid sinus was most common (65.6%), followed by high riding (54.9%) or dehiscent jugular bulb (14.4%). Dehiscent internal carotid artery canal (3.1%) and superior semicircular canal (4.1%) were occasionally identified, while arteriovenous fistula, arterial aneurysm and tumors arising from the JF region or cerebellopontine angle were rarely encountered.Conclusion Structural abnormalities of the JF and adjacent structures may predispose to the development of PT. Knowledge of these anatomical variants in the JF region may help establish a clinical strategy for addressing PT.
Keywords: pulsatile tinnitus; jugular foramen; structural anomaly; sigmoid sinus; jugular bulb; dehiscent